THE DEVELOPMENT OF A CREATIVE MIMA (MIND-MAPPING) ENGLISH BOOK FOR SUPPLEMENTING STUDENTS LEARNING MATERIAL - Lulita Ari Anggraini; Dwi Putri Hartiningsari (UIBU, 2023)
This study aims to develop a creative supplement book, MIMA English Book, for supplementing student learning material. Implementing a mind map helps summarize learning material and stimulate the students to have a better understanding of learning English subject. This study uses research and development methods using a quasi-experimental research design. The population of this study was students of class X, SMA Negeri 2 Trenggalek, especially in class X MIPA 1 which consisted of 33 students. Methods of data collection using interviews, questionnaires, observations, and tests. From the results of research that researchers have carried out, it was found that 1) The MIMA English Book was developed according to the student needs questionnaire and the results of interviews, 2) Feasibility validation which showed that the MIMA English Book presented materials and media that deserved to be tested, 3) Positive feedback from students against the MIMA English Book, and 4) The results of the t-test showed that there was a significant effect of the use of the MIMA English Book on students' learning in English. In conclusion, the MIMA English Book is an effective learning medium for supplementing student learning material in learning English.